Genomic analysis of Ranavirus and exploring alternative genes for phylogenetics. Issue 4 (4th November 2020) - Yu, Zehui; Zhang, Wenjie; Gu, Congwei; Chen, Jindong; Zhao, Mingde; Fu, Lu; Han, Jianhong; He, Manli; Xiao, Qihai; Xiao, Wudian; He, Lvqin; Zhang, Zhimin
Abstract: Ranaviruses can infect both captive and wild cold‐blooded vertebrates, leading to significant economic and environmental losses. With the cases of ranavirus infection increasing, many ranavirus genomic sequences were published, but little is known about ranavirus taxonomy on a whole‐genome level. In this study, 44 ranaviruses core genes were identified in 32 ranaviruses genome sequences by using PanX. The neighbour‐joining phylogenetic trees (NJ‐tree) based on 44 ranaviruses core genes and 24 iridoviridae core genes and composition vector phylogenetic tree (CV‐Tree) based on whole genome were constructed. The three of phylogenetic trees showed that 32 ranavirus isolates can be divided into 4 different subgroups including SGIV‐like, EHNV‐like, FV3‐like and CMTV‐like, and subgroups taxonomic position of three phylogenetic trees were consistent. However, the phylogenetic position of ToRV could not be determined if it belongs to FV3‐like or CMTV‐like group. Subsequently, we carried out dot plot analysis and confirmed that ToRV should belong to CMTV‐like group. Based on dot plot analysis and phylogenetic trees, the taxonomic classification of ranaviruses was confirmed. Finally, four genes which are suitable for the construction of phylogenetic tree were selected from ranavirus core genes by recombination analysis, substitution saturation analysis and single‐gene phylogenetic analysis. Phylogenetic tree based on concatenated sequences of the four selected genes showed that the classification of subgroups was identical with three of the phylogenetic trees. Conclusion: Our results confirmed taxonomic identification of ranaviruses; the four selected genes used in phylogenetic analysis will make taxonomic identification more convenient and accurate.